Corporate Tax Avoidance: Kontribusi Mekanisme Corporate Governance dan Corporate Social Responsibility Pada Perusahaan Industri Manufaktur Sektor Industri Dasar dan Kimia Yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2018 - Ai Hendrani; Dadan Ramdhani; Thika Febriani; Sriyani Sriyani (STATERA: Jurnal Akuntansi dan Keuangan, 2020)
The purpose of this study is to examine the effect of the corporate governance mechanism using indicators of institutional ownership, independent commissioners, audit committee and managerial ownership and corporate social responsibility on corporate tax avoidance, empirical studies on basic industrial companies and chemicals listed on the Indonesia Stock Exchange. in 2014-2018. The research method used is quantitative research methods. Determination of the sample in this study is by purposive sampling technique, in order to obtain a research sample of 30 companies with a total of 150 (30 x 5 years) observations that match the specified characteristics. The data analysis technique used in this study is multiple linear regression analysis. which is done using the help of IBM SPSS 23.0 software. The results of this study show that institutional ownership, audit committee and managerial ownership have a positive effect on corporate tax avoidance. Independent commissioners have no effect on corporate tax avoidance. And corporate social responsibility has a negative effect on corporate tax avoidance.